2015
DOI: 10.1101/026393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epistasis and destabilizing mutations shape gene expression variability in humans via distinct modes of action

Abstract: Increasing evidence shows that, like phenotypic mean, phenotypic variance is also genetically determined, but the underlying mechanisms of genetic control over the variance remain obscure. Here, we conducted variance-association mapping analyses to identify expression variability QTLs (evQTLs), i.e., genomic loci associated with gene expression variance, in humans. We discovered that common genetic variations may contribute to increasing gene expression variability via two distinct modes of action—epistasis an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Specifically, the Uruguayan population is admixed, with a predominance of European contribution, and a Native American and African contribution of 10.4% and 5.6%, respectively [68,69]. Common genetic variation affects expression variability [70], as well as the admixtured genome structure [71,72], stressing the necessity of population-specific transcriptome analyses or alternatively including diversity in high throughput population analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the Uruguayan population is admixed, with a predominance of European contribution, and a Native American and African contribution of 10.4% and 5.6%, respectively [68,69]. Common genetic variation affects expression variability [70], as well as the admixtured genome structure [71,72], stressing the necessity of population-specific transcriptome analyses or alternatively including diversity in high throughput population analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that both common and rare genetic variants may confer regulatory function to contribute to gene expression dispersion (Hulse and Cai, 2013 ; Wang et al, 2014 ; Zeng et al, 2015 ). In particular, common genetic variants contribute to gene expression variability via distinct modes of action—e.g., epistasis and destabilizing mutations (Wang et al, 2015 ). Rare and private regulatory variants have been found to be responsible for extreme gene expression in outlier samples (Montgomery et al, 2011 ; Zeng et al, 2015 ; Zhao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that both common and rare genetic variants may confer regulatory function to contribute to gene expression dispersion [50][51][52] . In particular, common genetic variants contribute to gene expression variability via distinct modes of action-e.g., epistasis and decanalization 53 . Rare and private regulatory variants have been found to be responsible for extreme gene expression in outlier samples 52,54,55 .…”
Section: Evidence For the Aging Effect On Gene Expression Dispersionmentioning
confidence: 99%